1965
DOI: 10.1016/s0006-3495(65)86700-5
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray and Ultraviolet Sensitivity of Synchronized Chinese Hamster Cells at Various Stages of the Cell Cycle

Abstract: Populations of Chinese hamster cells, synchronized by selecting for cells at or close to division, were exposed to 250 kvp x-rays and to ultraviolet light at different stages of the cell cycle and colony-forming ability examined thereafter. These cells were found to be most resistant to x-rays during the latter part of the DNA synthetic period (S) and to be about equally sensitive before (G(1)) and after (G(2)) this period. Multitarget type curves of the same slope (D(o) approximately 200 rad) only approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

1967
1967
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(51 citation statements)
references
References 21 publications
(40 reference statements)
4
47
0
Order By: Relevance
“…(Similar studies relative to the variation of radiation-induced cell killing through the cycle of Chinese hamster cells have been reported [10] .) We present here our results with this antibiotic and we will report elsewhere a detailed comparison between cycle-dependent killing due to actinomycin D, radiation, and the bifunctional alkylating drug nitrogen mustard when these agents are used singly and together .…”
Section: Introductionsupporting
confidence: 60%
“…(Similar studies relative to the variation of radiation-induced cell killing through the cycle of Chinese hamster cells have been reported [10] .) We present here our results with this antibiotic and we will report elsewhere a detailed comparison between cycle-dependent killing due to actinomycin D, radiation, and the bifunctional alkylating drug nitrogen mustard when these agents are used singly and together .…”
Section: Introductionsupporting
confidence: 60%
“…Nab-paclitaxel induced mitotic arrest that lasted for 4 days after administration, although it peaked at 9 h. Earlier studies showed that solvent-based taxane -induced G 2 -M arrest is a major mechanism underlying radioenhancement produced by these agents (33) because G 2 -M cells are known to be more radiosensitive than cells in other phases of the cell cycle (34). Although this mechanism was likely involved in the presently observed enhancement of tumor radioresponse, it probably was not the dominant mechanism because radiation delivered at the peak of mitotic arrest was not the most effective combination schedule (enhancement factor = 1.3).…”
Section: Discussionmentioning
confidence: 99%
“…The effects noted though were sometimes small, and work with asynchronous ce 11 s has the added compl i cat i on that effects observed represent that of a heterogeneous population. It is well known that the radiation sensitivity of mammalian cells varies dramatically through the cell cycle (Terasima and Tolmach, 1961;Sinclair and Morton, 1965). …”
Section: Synchronized Cellsmentioning
confidence: 99%